IMPLEMENTASI UNDANG-UNDANG NOMOR 24 TAHUN 2007 TENTANG PENANGGULANGAN BENCANA DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Eko Adi Wibowo; Evi Satispi (SWATANTRA, 2017)
The study aims to how the implementations of low No. 24 of 2007 on disaster management in the pro- vince on D.I Yogyakarta. With a view of the side of the policy instrument and its implementation any discreation when viewed from the application of technical standard in use which generally include, institutional, human resources equipment stan- dard and operationing procedure standart (SOP). The method used in the research is descriptive qualitative method, as informant is staff on Natio- nal Board for Disaster Management and Local staf of District Board for Disaster Management Province of D.I Yogyakarta. Instrument used in assessing the two indicators above is by interview, literature stu- dy and observation. The result of studies have found that both indi- cators in policy instrument showed positive result, so that the implementation of the law number 24 of 2007 on disasters management in the province of D.I Yogyakarta will be going.